Essential oil composition of Artemisia stelleriana Besser from India. Issue 5 (2nd September 2016) - Padalia, Rajendra C.; Verma, Ram S.; Chauhan, Amit; Goswami, Prakash; Chanotiya, Chandan S.
Abstract: Artemisia stelleriana Bess. (Asteraceae), commonly known as 'dusty miller' or 'beach wormwood', is a perennial shrub that is used traditionally as a carminative and in the treatment of peptic ulcer. In this study, the essential oil composition of fresh aerial parts of A. stelleriana from India was analyzed using gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). Altogether, fifty-two constituents, forming 92.3% of the total oil compositions were identified, representing 49.5% of monoterpenoids and 42.8% of sesquiterpenoids. 1, 8-Cineole (29.5%), germacrene D (5.6%), vulgarone B (3.1%), davanone B (3.0%), artedouglasia oxides (22.5%) viz., artedouglasia oxide A (8.0%), artedouglasia oxide C (5.5%), artedouglasia oxide D (5.0%) and artedouglasia oxide B (4.0%) were identified as the major constituents of the essential oil. This is the first report on essential oil composition of A. stelleriana from India.